Nonsyndromic bilateral multiple retained primary incisors in mandibular arch: Rare case report - D Deepa; Nazar Rana; K V Arun Kumar (Wolters Kluwer Medknow Publications, 2016)
A disturbed eruption process creates a clinical situation that is challenging to diagnose and treat. The clinical arena of tooth eruption disorders includes both syndromic and nonsyndromic problems varying from delayed eruption to a complete failure of eruption or sometimes retained primary teeth. This paper reports a rare case of retained bilateral primary incisors on mandibular arch in a systemically healthy patient with eruption of the permanent central and lateral incisors bilaterally.